Hubungan Emotional Eating dan Pola Konsumsi Makan dengan Obesitas pada Mahasiswa Tingkat Akhir - Alifia Auliannisaa; Bambang Wirjatmadi (Universitas Airlangga, 2023)
Background: Obesity is a nutritional problem due to an imbalance in nutrient intake with nutrition needs. Many factors can influence the development of obesity, such as eating behavior and wrong eating patterns. Final year students are included in the group of early adults who are prone to experiencing academic stress which can affect their eating behavior and eating patterns. Objectives: The purpose of this study was to analyze the relationship between emotional eating and eating patterns with obesity in final year students at the Faculty of Public Health Universitas Airlangga in 2022. Methods: Case-control research design was used in the study, with a sample of 19 students in the overweight and obesity group and 19 students in the non-obese group. Samples were obtained by using a simple random sampling method. Online interviews were used as a data collection method with Dutch Eating Behavior Questionnaire (DEBQ) and Food Frequency Questionnaire (FFQ). Data were analyzed by Chi-Square statistical test. Results: The result of this study showed that there was no statistically significant relationship between emotional eating with obesity (p=0,501) and there was a statistically significant relationship between food consumption patterns with obesity (p=0,022) with OR value = 4,8, which means that students who predominantly consume obesogenic foods have a 4,8 times greater risk of obesity when compared to students who predominantly consume vegetables and fruit. Conclusions: The food consumption pattern has a significant relationship with obesity. Students should reduce their intake of obesogenic foods and increase their fiber intake, namely vegetables and fruit so as to reduce the risk of obesity.